Generation and application of monoclonal antibodies against CD4-1 and CD8α for characterizing T cell subsets in grass carp (Ctenopharyngodon idella) - Haokai Chen; Ming Geng; Kang Li; Zhichao Fang; Yating Zhu; Yuqing Yang; Shiqi Tang; Jingfeng Ding; Jiansong Zhang; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2026)

The fluidization dynamics of binary particles in a supergravity swirling liquid-solid fluidized bed using coupled MPPIC-VOF approach - Hailong Tang; Jingfeng He; Liangyu Yao; Dongyao Wang; Lixiang Fu; Bin Yang; Lingtao Zhu; Yuhao Liu (Chemical Engineering Journal, 2026)

Toward environmentally stable magnesium metal anodes via Bi interphase engineering for rechargeable magnesium batteries - Sitong Liang; Yuhang Chen; Xiaojin Lian; Zhimeng Tang; Lu Zhang; Xinwei She; Baihua Qu; Jingfeng Wang (Chemical Engineering Journal, 2026)

Dietary quercetin enhances T cell immunity and disease resistance in tilapia via modulating antioxidant and inflammatory responses - Haokai Chen; Jingfeng Ding; Yuqing Yang; Shiqi Tang; Qiqi Jiang; Yuying Zheng; Yating Zhu; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

N-acetylcysteine enhances antioxidant capacity and anti-bacterial immunity of T cells in tilapia by regulating KEAP1-NRF2 axis - Kang Li; Shiqi Tang; Jingfeng Ding; Yuqing Yang; Haokai Chen; Qiqi Jiang; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

Evolution characteristics and energy loss of the swirling flow in a gradient supergravity rotating field used for separation - Hailong Tang; Jingfeng He; Liangyu Yao; Lixiang Fu; Bin Yang; Lingtao Zhu (Journal of Environmental Chemical Engineering, 2026)

Dietary ferulic acid boosts the immunity and antioxidant activity of T lymphocytes in Nile tilapia (Oreochromis niloticus) challenged with Aeromonas hydrophila - Jiansong Zhang; Yuqing Yang; Jingwen Chang; Jingfeng Ding; Shiqi Tang; Yishan Lu; Xiumei Wei; Jialong Yang (Fish & Shellfish Immunology, 2026)

Optimization of friction medium rod shape and its enhanced pre-concentration of coal-hosted graphite ore by triboelectric separation - Yuhao Liu; Jingfeng He; Wenjie Tang; Shuaixing Shi; Lingtao Zhu; Bin Yang (Minerals Engineering, 2026)

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

A strategy for effective flocculation and sedimentation of coal gasification fine slag using a composite reagent system of CTAC/PDADMAC/NPAM - Jiawei Wu; Jingfeng He; Xinyao Wang; Hailong Tang; Bin Yang; Lingtao Zhu (Journal of Water Process Engineering, 2025)

Gradient multi-component interphase enabling highly reversible magnesium metal anode in fluorinated alkoxyborate-based electrolytes - Yuhang Chen; Yiming Zhang; Zhimeng Tang; Zhenyu Zhang; Le Tong; Xuemin Gan; Xing Shen; Guangsheng Huang; Qian Li; Baihua Qu; Fusheng Pan; Jingfeng Wang (Chemical Engineering Journal, 2025)

Supergravity separation: An innovative strategy for efficient cleaning and upgrading of coal gasification slag waste - Hailong Tang; Jingfeng He; Lixiang Fu; Jiahui Zhang; Liangyu Yao; Bin Yang; Lingtao Zhu; Shihai Guo (Waste Management, 2025)

Insights into contrastive cellulose nanofibrils assembly and nanocrystals catalysis from dual regulations of plant cell walls - Yuanhang Ai; Hailang Wang; Peng Liu; Hua Yu; Mengdan Sun; Ran Zhang; Jingfeng Tang; Yanting Wang; Shengqiu Feng; Liangcai Peng (Science Bulletin, 2024)

Cleaning and upgrading of low-rank coal using a novel rotary triboelectric separator with the polyvinyl chloride as friction medium - Bin Yang; Lingtao Zhu; Jingfeng He; Bin Liu; Shibo Huang; Hao Chen; Wenjie Tang (Fuel, 2024)

Assessment of methane emissions from pressure regulation stations in China - Fei Li; Jianfeng Tang; Zhengyi Xie; Xuanke Li; Yuchen Niu; Tong Li; Yifan Wang; Jingfeng Zhang; Zhenyu Gao (Atmospheric Pollution Research, 2024)

AIEgen-based nanotherapeutic strategy for enhanced FLASH irradiation to prevent tumour recurrence and avoid severe side effects - Meng Lyu; Tianfu Zhang; Yang Li; Jingfeng Xiang; Daoming Zhu; Ligang Xia; Bin Guo; Youhua Xu; Haijun Yu; Benzhong Tang (Chemical Engineering Journal, 2023)

Structural and species diversity explain aboveground carbon storage in forests across the United States: Evidence from GEDI and forest inventory data - Erin T.H. Crockett; Jeff W. Atkins; Qinfeng Guo; Ge Sun; Kevin M. Potter; Scott Ollinger; Carlos A. Silva; Hao Tang; Christopher W. Woodall; Justin Holgerson; Jingfeng Xiao (Remote Sensing of Environment, 2023)

BsEXLX of engineered Trichoderma reesei strain as dual-active expansin to boost cellulases secretion for synergistic enhancement of biomass enzymatic saccharification in corn and Miscanthus straws - Chengbao Xu; Tao Xia; Hao Peng; Peng Liu; Yihong Wang; Yanting Wang; Heng Kang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

An amino acid duplication/insertion in the Bm126 gene of Bombyx mori nucleopolyhedrovirus alters viral gene expression as shown by differential gene expression analysis - Jinshan Huang; Jingfeng Li; Chen Cheng; Xudong Tang; Xingjia Shen; Bifang Hao (Archives of Virology, 2019)

Condition dependence of advertisement calls in male African clawed frogs - Xiaocui Wang; Zhi-Jun Zhao; Yan Cao; Jianguo Cui; Yezhong Tang; Jingfeng Chen (Journal of Ethology, 2019)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Impacts of land use and socioeconomic patterns on urban heat Island - Junmei Tang; Liping Di; Jingfeng Xiao; Dengsheng Lu; Yuyu Zhou (International Journal of Remote Sensing, 2017)

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010 - Na Zhu; Peng Li; Jingfeng Yu; Yongdong Li; Jiuru Zhao; Han Xia; Shuang Tang; Zhong Zhang; Zheng Kou; Shiyu Yin; Zhaojun Fan; Tianxian Li (Virus Genes, 2013)

Development and evaluation of a new detection tool—visual DNA microarray for simultaneous and specific detection of human immunodeficiency virus type-1 and hepatitis C virus - Jingfeng Tang; Li Zhou; Lian Lian Duan; Yang Feng; Xuan Cao; Yefu Wang (Molecular Biology Reports, 2011)

Antioxidation activities of low-molecular-weight gelatin hydrolysate isolated from the sea cucumber Stichopus japonicus - Jingfeng Wang; Yuming Wang; Qingjuan Tang; Yi Wang; Yaoguang Chang; Qin Zhao; Changhu Xue (Journal of Ocean University of China, 2010)